Fast creation of dense MgB2 phase in wires made by IMD process. (1st September 2016) - Kováč, P; Hušek, I; Melišek, T; Kopera, L; Kulich, M
Abstract: Single-core MgB2 wires have been made by internal magnesium diffusion (IMD) into boron process. Heat treatments were performed at variable periods (4–90 min) for two adjusted temperatures 635 °C and 650 °C, with an overshoot of ≈20 °C after 5 min. Critical currents of differently treated MgB2 /Ti/GlidCop wires have been measured and related with the MgB2 layers. The fast creation MgB2 compound has been observed after 8 min annealing at both temperatures and showing the critical current maxima. The less uniform MgB2 containing cracks was created for longer annealing periods (≥10 min), which resulted in lowered critical currents and worsened thermal stability. The fast creation of dense MgB2 allows it to utilize a continual and short heat treatment process for high current density wires made by IMD.